What's the difference? : recreational culinary reference for the curious and confused - Warshaw, Brette (HarperWave, an imprint of HarperCollinsPublisher, 2021)
"Everything you ever wanted to know about culinary terms that the foodie is afraid to ask: Based on Brette Warshaw's eponymous newsletter, What's the Difference? Is an essential guide that explores all of the differences between kitchen essentials and cooking terms that even non-foodies are too embarrassed to ask about"--